2022
DOI: 10.1155/2022/4176595
|View full text |Cite|
|
Sign up to set email alerts
|

Immersive Learning Method of Ideological and Political Education under Big Data and Artificial Intelligence

Abstract: The study aims to explore the influence of big data on college students’ learning methods of ideological and political education (IPE) under artificial intelligence. First, the characteristics of big data are analyzed. Second, big data is introduced into IPE’s classroom teaching, and its influence on students’ learning methods is discussed. Finally, the questionnaire is designed to investigate students’ learning attitudes and teachers’ effectiveness. The results show that the scores of the students are poor, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The goal of ideological and political education (IPE) in universities and colleges is to continuously improve the ideological cultivation, political literacy, and moral cultivation of the students. IPE also aims to guide higher education students to establish a correct outlook on life, values, and the world [1]. However, there are certain distinct features of ideological and political teaching due to its strong theoretical nature.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of ideological and political education (IPE) in universities and colleges is to continuously improve the ideological cultivation, political literacy, and moral cultivation of the students. IPE also aims to guide higher education students to establish a correct outlook on life, values, and the world [1]. However, there are certain distinct features of ideological and political teaching due to its strong theoretical nature.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%